First record of Elasmus polistis (Hymenoptera: Eulophidae), parasitoid of Polistes versicolor (Hymenoptera: Vespidae), in Minas Gerais, Brazil - Gabriel Castro Jacques; Sheliane C. C. Francisco; Luis Cláudio P. Silveira (Sociobiology, 2022)
The social wasps of the order Hymenoptera, family Vespidae and subfamily Polistinae, perform important ecological functions such as pollination and predation, including pest insects, and can be an important resource in biological control. Some species of parasitoids attack nests of social wasps causing mortality in the early stages of development, thus impairing the biological control exercised by these insects. This study aimed to verify the occurrence and identify parasitoids in nests of Polistes versicolor Olivier, 1971, at the Instituto Federal de Educação, Ciência e Tecnologia de Minas Gerais (IFMG) - Campus Bambuí, Brazil. In total, 14 nests of P. versicolor were collected. The parasitism rate was 28.57%, and parasitoids were recorded in four of the 14 nests collected. The presence of parasitized nests may be due to the absence of a protective envelope, typical of the nest of P. versicolor. The emerged parasitoid belongs to the species Elasmus polistis Burks, 1971 (Hymenoptera: Eulophidae), a species identified in nests of social wasps only in the state of Rio Grande do Sul, southern Brazil. To the best our knowledge, this is the first study that shows the occurrence of E. polistis parasitizing social wasps in the state of Minas Gerais, southeastern Brazil.